Properties of Nanoscale Particles on the Basis of Metals Localized Into Biological Tissues - Shpak, A.P.; Brik, A.B.; Karbovskiy, V.L.; Rosenfeld, L.G. (Успехи физики металлов, 2003)
The nanoscale solid-state particles localized into high-mineralised biological tissues (tooth enamel, bone) and into weakly-mineralised tissues (organic tissue of mollusc shells, tissue of brain) are considered. The properties of the nanoscale solid-state particles formed on the basis of metallic ions are studied. The data about properties of the nanoscale particles localized into above-mentioned biological tissues are obtained mainly by electron paramagnetic resonance (EPR). high-mineralised tissues, the problems bound with hierarchy of an internal structure, interaction mechanisms of an organic and mineral substance, an anisotropy of their structure, and impurity crystalline phases are considered. Описаны наноразмерные частицы твердого тела, локализованные в высокоминерализованных биологических тканях (эмаль зубов, кости) и в слабоминерализованных тканях (органическая ткань раковин моллюсков, ткани мозга). Изучены свойства этих наноразмерных частиц, которые сформированы на основе металлических ионов. Данные о свойствах наноразмерных частиц в вышеперечисленных биологических тканях получены в основном с помощью электронного парамагнитного резонанса. Для высокоминерализованных тканей рассмотрены вопросы, связанные с иерархией внутреннего строения, механизмами взаимодействия органического и минерального вещества, анизотропией структуры и примесными кристаллическими фазами. Описано нанорозмірні частинки твердого тіла, що локалізовані у високомінералізованих біологічних тканинах (емаль зубів, кістки) і в слабомінералізованих тканинах (органічна тканина раковин молюсків, тканини мозку). Вивчено властивості цих нанорозмірних частинок, сформованих на основі металічних іонів. Дані про властивості нанорозмірних частинок у вищевказаних біологічних тканинах отримано в основному за допомогою електронного парамагнітного резонансу. Для високомінералізованих тканин розглянуто питання, пов’язані з ієрархією внутрішньої будови, механізмами взаємодії органічної й мінеральної матерії, анізотропією структури і домішковими кристалічними фазами.